GOVERNMENT SUPPORT AND DIGITAL MARKETING CAPABILITY: ENHANCING DIGITAL MARKETING PERFORMANCE OF MSMES IN INDONESIA - Sugianto Sugianto (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study investigates how government support influences digital marketing performance (DMP) through the mediating role of digital marketing capability (DMC) among MSMEs in Pontianak City, Indonesia. Grounded in the Dynamic Capabilities Theory, the study aims to explain how external institutional support transforms into adaptive marketing competencies that enhance MSMEs’ competitiveness in digital markets.METHODOLOGY - A quantitative research design was employed using a structured questionnaire distributed to 250 MSME owners and managers. The sampling technique applied was purposive sampling. Data were analyzed using PLS-SEM to examine both direct and mediating effects. Measurement reliability and validity were confirmed through Cronbach’s Alpha, Composite Reliability, and Average Variance Extracted (AVE) criteria.FINDING - The results reveal that government support significantly and positively affects both DMC and DMP. Furthermore, DMC demonstrates a strong positive effect on DMP and mediates the relationship between government support and performance. These findings underscore that capability-building mechanisms are the primary pathway through which public interventions yield sustainable digital performance.